2021
DOI: 10.1002/hyp.14326
|View full text |Cite
|
Sign up to set email alerts
|

Tile drainage causes flashy streamflow response in Ohio watersheds

Abstract: Artificial subsurface (tile) drainage is used to increase trafficability and crop yield in much of the Midwest due to soils with naturally poor drainage. Tile drainage has been researched extensively at the field scale, but knowledge gaps remain on how tile drainage influences the streamflow response at the watershed scale. The purpose of this study is to analyse the effect of tile drainage on the streamflow response for 59 Ohio watersheds with varying percentages of tile drainage and explore patterns between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 58 publications
3
22
3
Order By: Relevance
“…TD substantially altered the streamflow events by increasing peaks by 14%, increasing volume by 2.3%, delaying event start time by 2 hr, and reducing the end time by 7 hr. As indicated by previous studies, TD is responsible for more short-term flashy streamflow events (De Schepper et al, 2017;Miller & Lyon, 2021;Rahman et al, 2014;Robinson et al, 1985). Our results indicated a considerable increase in seasonal streamflow volume due to TD.…”
Section: Effect Of Td On Regional Hydrologysupporting
confidence: 84%
See 1 more Smart Citation
“…TD substantially altered the streamflow events by increasing peaks by 14%, increasing volume by 2.3%, delaying event start time by 2 hr, and reducing the end time by 7 hr. As indicated by previous studies, TD is responsible for more short-term flashy streamflow events (De Schepper et al, 2017;Miller & Lyon, 2021;Rahman et al, 2014;Robinson et al, 1985). Our results indicated a considerable increase in seasonal streamflow volume due to TD.…”
Section: Effect Of Td On Regional Hydrologysupporting
confidence: 84%
“…However, the baseflow index is estimated as the ratio of total baseflow to the total streamflow is decreased by −9.10%. In other words, the impact of TD on direct runoff (or quick flow) is more substantial compared to baseflow (Miller & Lyon, 2021). Overall, TD has significant effects on most of the water balance components in the study domain.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, which had above average annual precipitation and March-July precipitation, watershed tile drainage percentage was significantly correlated with annual and March-July runoff and annual and March-July runoff ratios (Figure 3). These results are supported by recent research from Miller and Lyon (2021) who observed a flashier streamflow response in watersheds with high percentages of tile drainage in Ohio compared to watersheds with little to no tile drainage. The lack of relationship between tile drainage and annual or March-July runoff and runoff ratios during 2018 suggests that the presence of tile drainage amplifies the flashiness during wetter than average years in this region, while the effect is less noticeable in years with normal (or low) amounts of precipitation.…”
Section: Connections Between Tile Drainage Stream Discharge and Nutrient Transportsupporting
confidence: 81%
“…Other studies from Iowa indicated that tile drainage primarily affects the baseflow portion of the hydrograph (Schilling and Helmers, 2008a) and water exiting tile drains is primarily sourced from baseflow (Schilling and Jones, 2019). Contrasting results were recently reported in Ohio watersheds, whereby watersheds with extensive tile drainage had significantly lower streamflow recession constants and baseflow percentages, suggesting a flashier streamflow behavior in watersheds with high percentages of tile drainage (Miller and Lyon, 2021). The opposite pattern observed in Ohio watersheds compared to Iowa was hypothesized to be due to increased precipitation, decreased drainage capacity of soils derived from clay-and silt-sized glaciolacustrine deposits, and shallower water tables in Ohio compared to Iowa.…”
Section: Introductionmentioning
confidence: 74%
“…
Agriculture can impact aquatic ecosystems in many ways including increased nutrient concentrations (Goolsby et al, 2001), increased stream temperatures (Goss et al, 2014), increased sediment loads (Lamba et al, 2015), decreased hydraulic residence time (Herrman et al, 2010), and changes to the natural flow regime through flow alterations such as artificial drainage (Miller & Lyon, 2021;Schilling & Helmers, 2008) or water abstraction for irrigation (Matthaei et al, 2010). Collectively, these stressors can transform the structure and function of aquatic ecosystems (Blann et al, 2009), resulting in habitat loss, altered community composition, and declines in biodiversity (Burdon et al, 2013).
…”
mentioning
confidence: 99%